Unravelling Arbuscular Mycorrhizal Community in Kaolin Post-Mining and Tropical Heath Forest Ecosystems in Belitung Regency, Indonesia - Muhammad Hilman Aulia; Nampiah Sukarno; Rika Indri Astuti; Adi Yulandi; Kartini Kramadibrata; Sri Listiyowati (HAYATI Journal of Biosciences, 2026)
Arbuscular Mycorrhizal (AM) symbiosis plays a vital role in supporting plant growth in restored degraded land and natural forests. This study examined AM communities present within the root and the rhizosphere of kaolin post-mining land areas and tropical heath forests using both spore morphology and metagenomic approaches. Soil and plant root samples were collected from three distinct zones: the kaolin post-mining land, ecotone, and heath forest, and used to establish trap cultures with Pueraria javanica. Spore-based identification revealed nine AMF species belonging to five genera, with Acaulospora and Glomus being the most dominant. Metagenomic analysis of 18S rRNA sequences from colonized P. javanica roots revealed 33 AMF-associated Amplicon Sequence Variants (ASVs), dominated by Glomus and Rhizophagus. Diversity indices indicated medium diversity levels across all sites, with the ecotone showing the highest evenness and species richness. Differences in AM communities between morphological and molecular approaches highlight the importance of integrating both methods to understand their diversity comprehensively. This baseline information contributes to the potential use of AMF as bio-restoration agents in the kaolin post-mining ecosystems. To our knowledge, this is the first report of AM communities in the kaolin post-mining land and tropical heath forest.